Sistem Penjualan Tiket Pertandingan Sepak Bola Berbasis Web - Rizki Fadila; Fx Wisnu Yudo Untoro (Melek IT : Information Technology Journal, 2016)
Match tickets football generally is still sold at manual system , so that the spectator who want to buy a ticket for soccer match the ball must be standing in line at the counter the stadium. The sales of tickets in this way , can give rise to several problems , that is happened a long queue , the violence due to a prospective buyer who disorderly when standing in line , and a prospective buyer who have standing in line but ran out of tickets. Therefore given a solution by making a new system that is the ticket sales system football web-based. The system is built with using language programming php ( the personal home page ) hypertext preprocessor and mysql database. Methods used in the preparation of duty the end was sdlc methodology ( systems development life cycle ). On a system the sales of tickets a football game this web-based , buyers have to input nik correctly and have a balance sufficient. If the purchase of successfully , customers will get a view tickets a football game that can be molded own. With this system , ticket buyers a football game will no longer need to queue up outside the stadium and brokering gradually diminishing.